Development of small molecule inhibitors targeting TGF-β ligand and receptor: Structures, mechanism, preclinical studies and clinical usage - Wang, Hao; Chen, Meiling; Sang, Xiaohong; You, Xuefu; Wang, Yucheng; Paterson, Ian Charles; Hong, Wei; Yang, Xinyi (Elsevier, 2020)
Transforming growth factor-β (TGF-β) is a member of a superfamily of pleiotropic proteins that regulate multiple cellular processes such as growth, development and differentiation. Following binding to type I and II TGF-β serine/threonine kinase receptors, TGF-β activates downstream signaling cascades involving both SMAD-dependent and -independent pathways. Aberrant TGF-β signaling is associated with a variety of diseases, such as fibrosis, cardiovascular disease and cancer. Hence, the TGF-β signaling pathway is recognized as a potential drug target. Various organic molecules have been designed and developed as TGF-β signaling pathway inhibitors and they function by either down-regulating the expression of TGF-β or by inhibiting the kinase activities of the TGF-β receptors. In this review, we discuss the current status of research regarding organic molecules as TGF-β inhibitors, focusing on the biological functions and the binding poses of compounds that are in the market or in the clinical or pre-clinical phases of development. © 2020 Elsevier Masson SAS